The relationships between the multidimensional planned behavior model, green brand awareness, green marketing activities, and purchase intention - Baltaci, Duygu Cinar; Durmaz, Yakup; Baltaci, Furkan; Baltacı, Furkan (Wiley)
IntroductionThis study investigates the determinants impacting consumer purchasing behavior.MethodsUtilizing multidimensional planned behavior theory alongside measures of brand awareness and green brand awareness, this study examines the mediating role of multidimensional planned behavior theory. Empirical data were gathered through a survey conducted among Generation Z university students, yielding 638 responses. Analysis was performed on 590 valid responses.ResultsFindings indicate that green marketing initiatives and green brand awareness positively influence consumers' purchase intentions. Subdimensions of the theory of planned behavior (TPB), namely, attitude, subjective norms, and perceived behavioral control, serve to strengthen these relationships and mediate the interaction process.ConclusionThis study contributes novel insights to the burgeoning field of green marketing literature, offering a structural model for firms and policymakers. It suggests that companies can effectively engage in informal consumer education through green marketing efforts, thereby influencing consumers' purchasing decisions via planned behavior. Moreover, such activities foster an increase in consumers' green brand awareness, providing companies with an opportunity to promote conscious consumer behavior. The study's utilization of the TPB is both timely and original, particularly in its alignment with the United Nations 2030 Sustainable Development Goals. This study investigates the mediating role of green marketing activities in the effect of green brand awareness on consumer purchase intention. A survey was conducted with university students in the Generation Z consumer class for empirical research. A total of 638 feedbacks were provided in the online survey application. The analyses were conducted on 590 valid survey data. image
Keywords: Generation Z; green awareness; green brand; green marketing; planned behavior; purchase intention